RESPONS MASYARAKAT TERHADAP DESAIN MEDIA SOSIALISASI PENCEGAHAN COVID-19 DI PROVINSI RIAU - Muhammad Badri (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2023)
This study aims to determine the public's response to the design of outdoor media in the form of posters, banners, and billboards that are used to socialize Covid-19 prevention in Riau Province. This study uses a quantitative approach with a survey method. Data collection was carried out through the distribution of online questionnaires with a total of 825 respondents. Research instruments include media exposure and responses to design concepts, images, colors, typography, message effectiveness, and their influence on the audience. This study found that banner media exposure was higher (78.2%) than billboards (76.8%) and posters (66.3%). But overall the response to the design elements of posters, banners, and billboards is in the high score range (61% -80%) which means good, even for messages, typography, and color on billboards media, it is close to a very high score range. This finding explains that outdoor media is still effectively used for health socialization, especially preventing the spread of Covid-19.